Legal Education - A Mandatory Condition Development Of Legal Consciousness And Legal Culture - Utemuratov Mahmut Azhimuratovich, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article examines the concept, goals, principles, forms and methods of legal education. About how legal education is a constant influence on the consciousness and behavior of an individual in order to realize certain views, values, and the formation of guidelines that ensure the purposeful activity of the state, public organizations and individual citizens to exchange legal experience: observance, application of legal norms and the use of them. Legal education is also considered as an integral part of the legal mechanism and can also be considered as a tool that affects the morality and legal consciousness of the subjects of legal relations.